# How to make loop and sum the result ??

5 views (last 30 days)
ali on 4 Jun 2014
Commented: Mahdi on 4 Jun 2014
I have this loop...
for i=1:3
A=x((i-1)*3+1);
B=x((i-1)*3+2);
C=x((i-1)*3+3);
R=A^2+B^3+A*c;
end
i have constriants D=7 or <7
so i need this costraint=D-C-M
let say M=2
my equestion is how can i have the sumuation result of C from loop three times and then add this sum to constraint equation???
Thank you.

Mahdi on 4 Jun 2014
for i=1:3
A(i)=x((i-1)*3+1);
B(i)=x((i-1)*3+2);
C(i)=x((i-1)*3+3);
R(i)=A^2+B^3+A*c;
end
Summation=sum(C);

ali on 4 Jun 2014
Thank you Mahdi for answer, but i want the result value of c in each loop after sum add to eq .. constraint =D-C( sum of result in each loop)- M
Mahdi on 4 Jun 2014
Just move the summation inside the for loop:
for i=1:3
A(i)=x((i-1)*3+1);
B(i)=x((i-1)*3+2);
C(i)=x((i-1)*3+3);
R(i)=A^2+B^3+A*c;
Summation(i)=sum(C);
end
In this case, each row of summation would correspond to the summation inside each iteration of the loop.

### Categories

Find more on Loops and Conditional Statements in Help Center and File Exchange

### Tags

No tags entered yet.

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!